2008
DOI: 10.1246/cl.2008.266
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Gene Delivery by pDNA/Chitosan Complexes Coated with Anionic PEG Derivatives that Have a Sugar Side Chain

Abstract: We developed pDNA/chitosan complexes coated with sugar-modified PEG-A/Cs, which are poly(ethylene glycol) derivatives with a side chain of carboxylic acid and sugar. The cationic pDNA/chitosan complexes were coated with anionic sugar-modified PEG-Cs, and anionic ternary complexes were formed. Coating the pDNA/chitosan complexes with maltose- or lactose-modified PEG-A/C (Mal–PEG-A/C or Lac–PEG-A/C, respectively) greatly promoted their stability in water and transfection efficiency in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, they also elicited serum‐induced aggregation and an absence of significant gene expression in tumor‐implanted mice . To overcome these issues, pDNA/chitosan complexes were coated with CS and anionic PEG derivatives in our previous study . Notably, the pDNA/chitosan/CS complexes reduced serum‐induced aggregation and induced high transgene expression in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they also elicited serum‐induced aggregation and an absence of significant gene expression in tumor‐implanted mice . To overcome these issues, pDNA/chitosan complexes were coated with CS and anionic PEG derivatives in our previous study . Notably, the pDNA/chitosan/CS complexes reduced serum‐induced aggregation and induced high transgene expression in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…10 To improve the stability and transgene expression of pDNA/chitosan complexes, Hashimoto et al 11,12 performed chemical modifications of chitosan with sugars. Furthermore, cationic pDNA complexes were coated with polyanions such as polyethylene glycol (PEG) derivatives, 13 hyaluronic acid (HA), [14][15][16][17] chondroitin sulfate (CS) 9,10,[18][19][20] and poly(γ-glutamic acid). 21 In our previous study, physicochemical properties and the transfection abilities of pDNA/chitosan complexes coated with CS were investigated and it was observed that CS demonstrates excellent gene carrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…To address these limitations, ternary complexes prepared by coating the cationic DNA/polycation complex with anionic polymer have been developed [49,50].…”
Section: Pdna/chitosan/anionic Polymer Ternary Complexesmentioning
confidence: 99%
“…Hashimoto et al developed the pDNA/chitosan complexes coated with lactose-modified PEG-C derivatives, namely pDNA/chitosan/Lac-PEG-C ternary complexes (Fig. 7) [50]. Zeta potential of the pDNA/chitosan/Lac-PEG-C ternary complexes became negative by coating the cationic pDNA/chitosan complexes with anionic Lac-PEG-C.…”
Section: Pdna/chitosan/anionic Polymer Ternary Complexesmentioning
confidence: 99%
“…[1][2][3][4] An interest in such electrostatic interactions lies in their similarity to biological systems; 7 such interactions between proteins and nucleic acids very likely play a role in the transcription process. 5 DNA/chitosan PECs, 8 chiosan/chondroitin sulfate PECs and chitosan/hyaluronate PECs 9 have been reported as gene and 10 Heparinoids are known to specifically interact with variety of functional proteins, including growth factors, cytokines, extracellular matrix components and adhesion molecules. [11][12][13] Thus, heparin may be useful as a therapeutic agent in various pathological conditions involving functional proteins.…”
Section: Introductionmentioning
confidence: 99%